Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2005 - Casas-Sánchez, José Miguel; Río-Iglesias, José Luis del; Teruel, Josefina (2005)
Since 1988, a stratified random summer bottom trawl survey are being carried out in Flemish Cap (NAFO Regulatory Area of Division 3M) by UE. From 2003 the traditional research vessel Cornide de Saavedra was replaced by the R/V Vizconde de Eza. The new vessel was calibrated and the indexes transformed. In 2004 year, the lack of time has not permitted to transform the biomass and abundance shrimp indexes of the whole series and only the 2003 and 2004 indexes from the R/V Vizconde de Eza were transformed to the R/V Cornide de Saavedra scale. In this paper, the series from 1988 to 2002 obtained with the R/V Cornide the Saavedra were transformed to make them comparable to the results obtained with the new vessel R/V Vizconde de Eza. The results of shrimp from the last survey on Flemish Cap in 2005 are presented and compared to those from previous years of the same series. Both biomass and abundance have increased significantly due to increasing of 3 age-class. The female biomass decreased, mainly due to declining of 5 and 6 year-classes. Also, in recent years (2004 and 2005) the youngest specimens (age 1) didn't appear in the catches, and they were only presents in the small size bag on the codend.